How to communicate Kaitoki Marae into a mainstream product? : an exegesis presented in partial fulfilment of the requirement for the degree Masters in Design at Massey University, Wellington, New Zealand - Takimoana, Hemi Witere Wimaihi Kirihora (Massey University, 2015)
This project aims to express Kaitoki Marae aspirations into a global arena by product communication. Proposing a contemporary visual language from the reconfiguration of customary elements fused with modern tools. Maori health model ‘Te Whare Tapa Wha’ by Dr Mason Durie metaphorical symbolism of a House is guiding knowledge for transitional zones and elements. This begins the building of a visual library. However project reflects upon cultural values to insure integrity of KaitokiMarae is retained.
Keywords: Design; Arts Maori; Mahi toi; Research Subject Categories::INTERDISCIPLINARY RESEARCH AREAS::Cultural heritage and cultural production